Adhesive functionalized ascorbic acid on CoFe2O4: a core–shell nanomagnetic heterostructure for the synthesis of aldoximes and amines. Issue 68 (11th November 2020) - Sorkhabi, Serve; Ghadermazi, Mohammad; Mozafari, Roya
Abstract : Heterogeneous catalysts were prepared by the anchoring of cobalt and vanadium on the surface of CoFe2 O4 coated with ascorbic acid. Abstract : This paper reports on the simple synthesis of novel green magnetic nanoparticles (MNPs) with effective catalytic properties and reusability. These heterogeneous nanocatalysts were prepared by the anchoring of Co and V on the surface of CoFe2 O4 nanoparticles coated with ascorbic acid (AA) as a green linker. The prepared nanocatalysts have been identified by scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray atomic mapping, thermogravimetric analysis, X-ray powder diffraction, vibrating sample magnetometer analysis, coupled plasma optical emission spectrometry and Fourier transform infrared spectroscopy. The impact of CoFe2 O4 @AA-M (Co, V) was carefully examined for NH2 OH·HCl oximation of aldehyde derivatives first and then for the reduction of diverse nitro compounds with sodium borohydride (NaBH4 ) to the corresponding amines under green conditions. The catalytic efficiency of magnetic CoFe2 O4 @AA-M (Co, V) nanocatalysts was investigated in production of different aldoximes and amines with high turnover numbers (TON) and turnover frequencies (TOF) through oximation and reduction reactions respectively. Furthermore, the developed environment-friendly method offers a number of advantages such as high turnover frequency, mild reaction conditions, high activity, simple procedure, low cost and easy isolation of the products from the reaction mixture by an external magnetic field and the catalyst can be reused for several consecutive runs without any remarkable decrease in catalytic efficiency.